Drogas Modificadoras de la Artritis Reumatoide (DMAR) Disease Modifying Antirheumatic Drugs (DMARD) - José Francisco Díaz-Coto (Acta Médica Costarricense, 2011)
El nuevo paradigma terapéutico de la artritis reumatoide establece que todo paciente con actividad de la enfermedad debe recibir alguna droga modificadora de la artritis reumatoide. Estas drogas reciben este nombre ya que han demostrado en estudios clínicos controlados modificar el curso natural de la enfermedad. The new paradigm for the treatments of rheumatoid arthritis stablish that all patients suffering disease this should receive some drugs which modifys rheumatoid arthritis. These drugs are so named because according to the controlled clinical studies they have shown the ability of modifying the natural course of the diseases.